The Bilingual Lexicon, Back and Forth: Electrophysiological Signatures of Translation Asymmetry - Garcia-Serrano, A (Elsevier Ltd, 2022)
Mainstream theories of first and second language (L1, L2) processing in bilinguals are crucially informed by word translation research. A core finding is the translation asymmetry effect, typified by slower performance in forward translation (FT, from L1 into L2) than in backward translation (BT, from L2 into L1). Yet, few studies have explored its neural bases and none has employed (de)synchronization measures, precluding the integration of bilingual memory models with neural (de)coupling accounts of word processing. Here, 27 proficient Spanish-English bilinguals engaged in FT and BT of single words as we obtained high-density EEG recordings to perform cluster-based oscillatory and non-linear functional connectivity analyses. Relative to BT, FT yielded slower responses, higher frontal theta (4–7 Hz) power in an early window (0–300 ms), reduced centro-posterior lower-beta (14–20 Hz) and centro-frontal upper-beta (21–30 Hz) power in a later window (300–600 ms), and lower fronto-parietal connectivity below 10 Hz in the early window. Also, the greater the behavioral difference between FT and BT, the greater the power of the early theta cluster for FT over BT. These results reveal key (de)coupling dynamics underlying translation asymmetry, offering frequency-specific constraints for leading models of bilingual lexical processing. © 2021 IBRO